HADITS TENTANG ALAT DAN MEDIA PENDIDIKAN - Marlina Marlina (ADISAM PUBLISHER, 2025)
Prophet Muhammad Saw is a guide and teacher for all Muslims, in every word, behavior or other from him are lessons that we can take wisdom from. No exception in terms of learning or seeking knowledge, he not only conveyed lessons but also paid attention to all aspects that support the learning, namely in terms of study time, place, schedule, to the media used in learning. In essence, the learning process is communication, therefore, learning media can be understood as a communication medium used in the learning process. Thus, it can be concluded that learning media is a physical medium used during learning in the form of message delivery. The goal is for a communication interaction process to occur between teachers and students